The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1093/ijnp/pyac035
|View full text |Cite
|
Sign up to set email alerts
|

Positive Allosteric Modulation of α5-GABAA Receptors Reverses Stress-Induced Alterations in Dopamine System Function and Prepulse Inhibition of Startle

Abstract: Background Up to 64% of patients diagnosed with PTSD experience psychosis, likely attributable to aberrant dopamine neuron activity. We have previously demonstrated that positive allosteric modulators of α5-GABAARs (α5-PAMs) can selectively decrease hippocampal activity and reverse psychosis-like physiological and behavioral alterations in a rodent model used to study schizophrenia; however, whether this approach translates to a PTSD model remains to be elucidated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(37 citation statements)
references
References 76 publications
3
15
0
Order By: Relevance
“…The FAB model has already been commercialized and used for drug discovery and development, and our study provides evidence that this model can also serve as a useful tool to further investigate AD with comorbid psychosis, allowing for the identification of novel targets in order to develop therapeutic interventions for this devastating disorder. Indeed, drugs targeting α5 GABA-A receptors are of great interest, and are highly expressed in the hippocampus; they have been shown to have pro-cognitive and antipsychotic-like effects in vivo [ 82 , 122 , 123 , 124 ]. The results reported herein suggest that such compounds may have therapeutic utility for psychosis present in elderly AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The FAB model has already been commercialized and used for drug discovery and development, and our study provides evidence that this model can also serve as a useful tool to further investigate AD with comorbid psychosis, allowing for the identification of novel targets in order to develop therapeutic interventions for this devastating disorder. Indeed, drugs targeting α5 GABA-A receptors are of great interest, and are highly expressed in the hippocampus; they have been shown to have pro-cognitive and antipsychotic-like effects in vivo [ 82 , 122 , 123 , 124 ]. The results reported herein suggest that such compounds may have therapeutic utility for psychosis present in elderly AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, genome‐wide changes in the epigenetic machinery modulate the mechanisms underlying developmental and degenerative neuronal dysfunctions associated with other neurological diseases, such as Parkinson's disease and epileptic encephalopathy, 19,20 with putative effects on comorbidities of neurological diseases and psychiatric disorders on which phytocannabinoids can exert potential medicinal properties. Dysfunction in dopaminergic system activity in pilocarpine‐induced epilepsy was reported in literature 21 . Although many studies are still needed, changes in DNA methylation and the expression levels of genes and proteins associated with D 2 and D 3 dopaminergic receptors have also been demonstrated in brain areas such as the prefrontal cortex, nucleus accumbens, ventral tegmental area and hippocampus, areas potentially damaged in neurological disorders and other neuropsychopathologies.…”
Section: Introductionmentioning
confidence: 96%
“…Dysfunction in dopaminergic system activity in pilocarpine-induced epilepsy was reported in literature. 21 Although many studies are still needed, changes in DNA methylation and the expression levels of genes and proteins associated with D 2 and D 3 dopaminergic receptors have also been demonstrated in brain areas such as the prefrontal cortex, nucleus accumbens, ventral tegmental area and hippocampus, areas potentially damaged in neurological disorders and other neuropsychopathologies. A crosstalk between the transcriptional regulation of D 2 dopaminergic and CB1 cannabinoid receptors was already described in schizophrenia, 22 a psychiatric disorder in which D 3 dopaminergic receptor gene expression was reported to be reversed by a peripubertal treatment with CBD.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we posit that augmenting the function of α5GABA A Rs in the ventral hippocampus (vHipp) will likely have the same effect and normalize dopamine system function and behavior in a stress-based model displaying psychosis-like pathology. Indeed, we have previously demonstrated that this is the case in animal models used to study both schizophrenia and posttraumatic stress disorder (PTSD) where aberrant dopamine system function is present ( Donegan et al, 2019 ; McCoy et al, 2022 ; Perez et al, 2022 ). This evidence suggests that α5GABA A Rs may represent a viable therapeutic target for the treatment of psychosis across multiple disorders.…”
Section: Introductionmentioning
confidence: 98%
“…When administered chronically, α5-PAMs can reverse stress- or age-related neuronal atrophy in the hippocampus and prefrontal cortex ( Prevot et al, 2020 ; Bernardo et al, 2022 ). Additionally, α5-PAMs have shown promise in preclinical studies as antipsychotics ( Gill et al, 2011 ; McCoy et al, 2022 ; Perez et al, 2022 ). These results suggest that α5-PAMs may have therapeutic utility for multiple disorders, especially those in which aberrant hippocampal activity is present.…”
Section: Introductionmentioning
confidence: 99%